Africa: War is Business - Vellenga, Frank (Viewpoint Productions, 2006)
Verzio FF Submission An in-depth account of the connections between war, economy and the western consumer. “Africa: War Is Business” reveals how war economies come into being in Africa, and how they are maintained. The three-part series investigates the causes and effects of these economies, and where Western consumers fit into the equation. The film follows Prince Jaime de Bourbon de Parme, son of Princess Irene of the Netherlands, as he travels through Sierra Leone, Liberia and Congo looking for the cause of these wars in Africa and the role the continent's natural resources play in creating conflict. He wonders how countries so rich in these resources could be so overwhelmed by poverty.